1998
DOI: 10.1006/viro.1998.9201
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Exo III Motif of the Herpes Simplex Virus DNA Polymerase Gene Can Confer Altered Drug Sensitivities

Abstract: Two herpes simplex virus mutants containing mutated residues within the conserved Exo III motif of the polymerase gene were previously shown to be defective in 3'-5' exonuclease activity and exhibited extremely high mutation frequencies. In this study, we have shown that these mutants also exhibited higher resistance to phosphonoacetic acid and sensitivity to aphidicolin and all nucleoside analogs tested, including acyclovir and gangciclovir, compared to wild-type virus. Marker transfer experiments and sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Moreover, most KOS-induced substitutions were not found in Y7-induced mutants, thereby refuting the assumption that most substitutions observed in KOS mutants would also be isolated in Y7-induced mutants, if Y7 Pol is defective only in proofreading activity. Nevertheless, this suggests that Y7 Pol may also exhibit altered Pol activity, consistent with our previous finding that Y7 exhibits altered binding affinities to certain nucleoside analogs (12). Finally, the HSV-1 Pol might evolve base substitution mainly by misinsertion during DNA chain elongation.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, most KOS-induced substitutions were not found in Y7-induced mutants, thereby refuting the assumption that most substitutions observed in KOS mutants would also be isolated in Y7-induced mutants, if Y7 Pol is defective only in proofreading activity. Nevertheless, this suggests that Y7 Pol may also exhibit altered Pol activity, consistent with our previous finding that Y7 exhibits altered binding affinities to certain nucleoside analogs (12). Finally, the HSV-1 Pol might evolve base substitution mainly by misinsertion during DNA chain elongation.…”
supporting
confidence: 88%
“…Although the lack of sufficient common mutations could be due to the limited number of samples analyzed, the observation that most Y7-induced substitutions are Y7 specific suggested that Y7 Pol might exhibit an altered Pol activity in addition to the loss of its exonuclease activity. Consistent with this proposition is the observation that the Y7 recombinant exhibited different binding affinities to certain nucleoside analogs (12). However, the extents of the altered activity contributing to the accuracy of Pol's activity and whether it is essential for retaining Y7 Pol's activity in vivo require further study.…”
mentioning
confidence: 73%
“…Plaque reduction assays were performed to examine the drug sensitivity of each recombinant, as described previously (19). Since these recombinants are TK negative, only phosphonoacetic acid (PAA) and aphidicolin (APH) (Sigma) were used to analyze the Pol phenotype.…”
Section: Recombinant Virusesmentioning
confidence: 99%
“…Theoretically, one would expect to observe more identical substitutions in both groups if the exonuclease Pol does not have altered polymerase activity. The observation that recombinant Y7 (Y577H) virus also exhibits altered drug sensitivities relative to wild-type virus further supports that the Exo III motif has a role on the polymerization activity (Hwang et al, 1998) and that the polymerase and exonuclease domains of HSV-1 Pol are interdependent structurally and functionally, also as suggested by the overlap between conserved -region C and Exo III motif (Fig. 2).…”
Section: Exonuclease Deficient Polymerase Induces Altered Mutation Spmentioning
confidence: 55%